Analisis Yuridis Pemutusan Hubungan Kerja Yang Diputus Daluarsa Oleh Pengadilan Hubungan Industrial studi kasus putusan Nomor : 26/Pdt.Sus-PHI/2024/PN.SRG - Risdianto, Eko; Irayadi, Muhamad (PT Elaborium Elevasi Indonesia, 2025)
Termination of Employment is any kind of termination of employment of workers/laborers. Termination to obtain a livelihood, termination to finance the family and termination period for medical expenses, recreation and others, Some disputes over termination of employment are actually limited by a 1 year expiration period to make efforts to resolve disputes in Law No. 2 of 2004 concerning the Settlement of Industrial Relations Disputes, therefore in order to obtain the right to severance pay for Termination of Employment carried out by the company, the Workers filed a Termination of Employment Dispute Lawsuit to the Industrial Relations Court whose decision has expired, for that the problem is How is the Process of Termination of Employment Disputes in Law No. 2 of 2004 concerning the Settlement of Industrial Relations Disputes and What is the deadline for filing a termination of employment lawsuit in Law No. 2 of 2004 concerning the Settlement of Industrial Relations Disputes and the Constitutional Court Decision Number 94 / PUU-XXI / 2023 which was decided on February 29, 2024. The research method used in the author is normative legal research, namely, research on the application of law with a discussion of the Company's Actions that terminated the Employment of Andi Wiyono on the grounds that he was considered absent and to Indra Witanto on the grounds In connection with the action, persuading and ordering other employees not to accept sanctions given by the Company, the conclusion of which is that the Industrial Relations Court Decision which was decided to be out of date does not include the reasons regulated in Article 82 of Law Number 2 of 2004 concerning the Settlement of Industrial Relations Disputes.